Long-term effects of diabetes prevention: Evaluation of the M.O.B.I.L.I.S. program for obese persons - Jan Häußler; Friedrich Breyer (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
In response to the growing burden of obesity, public primary prevention programs against obesity have been widely recommended. Several studies estimated the cost effects of diabetes prevention trials for different countries and found that diabetes prevention can be costeffective. Nevertheless, it is still controversial if prevention conducted in more real-world settings and among people with increased risk but not yet exhibiting Increased Glucose Tolerance can really be a cost-effective strategy to cope with the obesity epidemic. We examine this question in a simulation model based on the results of the M.O.B.I.L.I.S program, a German lifestyle intervention to reduce obesity, which is directed on the high-risk group of people who are already obese. The contribution of this paper is the use of 4-year follow-up data on the intervention group and a comparison with a control group formed by SOEP respondents as inputs in a Markov model of the long-term benefits of this intervention due to prevention of type-2 diabetes.
Keywords: I12; H51; 330; diabetes prevention; cost-benefit analysis; Markov modeling